Peningkatan Peningkatan Hasil Belajar Matematika Materi Diagram Garis Melalui Penggunaan Media Papan Diagram pada Siswa Kelas IV SD: Peningkatan Hasil Belajar Matematika Materi Diagram Garis Melalui Penggunaan Media Papan Diagram pada Siswa Kelas IV SD - Anis Silvia Masithoh; Arfilia Wijayanti; Darsino (UNIB Press, 2024)
Learning outcomes are the final results achieved by students during the learning process. To improve student learning outcomes, one way is to use learning media. This is useful for improving the process of learning and teaching activities with the aim of achieving better learning goals. One of the media that can be used is PADI (Diagram Board) media which is used in data presentation materials. This research aims to determine the improvement in student learning outcomes in line diagram material through the Diagram Board Instruction (PADI) media at SDN Plamongansari 02 Semarang. This is demonstrated by an increase in student learning outcomes at the pre-cycle, Cycle I and Cycle II stages. At this stage, data was obtained from 24 students, that there were 13 students who got a score below the specified KKM, namely 75, and the average reached 71.42. Meanwhile, 11 students scored above the KKM. Furthermore, in Cycle I, 16 students scored above the KKM and 8 students scored below the KKM with an average score of 77.83. In cycle II, data was obtained for 24 students, there were 5 students who got a score below the KKM of 21%, while 19 students (79%) got a score above the KKM with an average score of 79.5.